2014
DOI: 10.1038/ijo.2014.52
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss maintenance in overweight subjects on ad libitum diets with high or low protein content and glycemic index: the DIOGENES trial 12-month results

Abstract: A higher protein content of an ad libitum diet improves weight loss maintenance in overweight and obese adults over 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 26 publications
1
87
2
5
Order By: Relevance
“…However, it was not statistically different than the other 2 conditions. This outcome replicates our previous finding (7), but both results diverge from past work that found that MRs significantly increase weight loss (3).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…However, it was not statistically different than the other 2 conditions. This outcome replicates our previous finding (7), but both results diverge from past work that found that MRs significantly increase weight loss (3).…”
Section: Discussioncontrasting
confidence: 42%
“…A second approach focuses on making numerous qualitative and quantitative modifications to nutritional intake. Studies have found support for reducing the energy density (ED) of the diet and manipulating the glycemic index and the protein content of the diet to increase weight loss (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, significant differences in the weight-loss tendency were found by others to be dependent on participant sex in different slimming interventions [45]. Additional findings concerning weight maintenance for longer periods of monitoring after weight loss seem to reinforce the role of protein in the success of managing weight regain [46].…”
Section: Approaches To Dietary Advice and Weight Maintenancementioning
confidence: 89%
“…In conclusion, between group comparison of the composition of weight loss and weight gain requires a careful matching for baseline body composition, for example when examining the effect of glycemic load [24] or glycemic index and protein intake [25] on weight regain after diet induced weight loss.…”
Section: Methodological Requirements Ii: Normalizing Changes In Fat Amentioning
confidence: 99%